Epidemiological Study Of Prevalence of Chronic Mastitis Cattle Farms of the General Organization of Cattle in the Middle Region of Syria (Journal of Hama University, 2022)
The Study Targeted to eleter mine the Prevalence of Chronic Mastitis in Dairy Cattle Herds in 2 Farm in General Organization of Cattle (Job Ramla and Homes Stations) in the middle Region of Syria and to eleter mine the most Bacterial Pathogens that caused such Type of Gland Inflammation. It was collected 82 Milk Samples from Chronic Mastitic Cattle cases during the period between October 2020 to April 2021. Results Reported that absolute Frequency of Chronic Mastitic Cattle in middle region of Syria 67 Dairy Cattle were Repotted 12.52% as over all prevalence faculty the infection was distract bucked in variant quarters in infected cattle the major percentages were in right lift back quarters. It was isolated several of bacterial pathogens. The most pathogens repotted were Escherichia coli as 28%, Follows by Staphylococcus auerus as 27%,then by Staphylococcus epidermidis as 13% , the next isolated pathogens were Staphylococcus Chromogens as 8% and Klebsiella, Streptococcus agalactiae 7%, Streptococcus dysgalactiae as 6% and finally by Staphylococcus saprophyticus wit 4%, as the lowest percentage.